Litter dynamics of selected multipurpose tree species used as pepper standards - Bino George (Department of Silviculture and Agroforestry, College of Forestry, 2005)
A field trial was conducted at Livestock Research Station, Thiruvazhamkunnu, Kerala during August 2002 - August 2003 to characterize the litter dynamics and nutrient flux associated with seven MPTS used as support for black pepper. The study covered quantification of litter production, litter decomposition, nutrient release pattern through litter route and the changes in soil properties and site productivity in terms of pepper yield. The pepper support tree species under study included, Casuarina equisetifolia J.R. & G. Forst, Macaranga peltata (Roxb) M.-A, Ailanthus triphysa (Dennst.) Alston, Artocarpus heterophyllus (Linn), Acacia auriculiformis (A. Cunn.) ex Benth, Grevillea robusta (A. Cunn.) ex R. Br. The experiment was superimposed on a pre-existing, fourteen- year- old pepper stand in a Randomized Block Design with three replications. Generally, moderate levels of litter production has been shown by different pepper support trees under investigation. Annual litter yield was maximum for Artocarpus (4653.63 kg ha-1) and Macaranga (4550.88 kg ha-1), while Ailanthus (2221.25 kg ha-1) yielded minimum. Nutrient level in litterfall varied between species. Maximum N content was associated with nitrogen fixing trees such as Acacia and Casuarina. The leaf litter decomposition rate was generally faster for all the species with almost 90 per cent mass loss within three months. Artocarpus showed faster rate of litter decomposition while Macaranga and Ailanthus were relatively slow decomposers. Unprecedented heavy mass loss was registered by Casuarina, Grevillea and Acacia from their litterbags owing to physical nature of the litter. All the selected tree species showed a characteristic biphasic pattern of litter decomposition. Decay coefficients ranged from 0.73 (Casuarina) to 0.19 (Macaranga). The exponential equations relating mass loss over time were worked out for all the species. The lignin content of the leaf litter was found to excerpt negative influence on the rate of litter decomposition. The general order of nutrient in terms of their releasing capacity from the decomposing litter was K>P>N. Acacia and Artocarpus registered faster rate of nutrient accretion. Changes in soil properties such as moisture content, pH and bulk density was marginal on account of the presence of tree species. Leguminous species like Acacia was found to improve the soil N content. Maximum rainfall interception was attributed to Artocarpus followed by Macaranga. The yield of pepper in terms of dry berry weight was maximum for Acacia (2.56 t ha-1) and Artocarpus (1.91 t ha-1). Better physical suitability, high lopped out turn and nutrient turnover potential suggest these species as ideal candidates for trailing pepper. However, the general reduction in soil physical and chemical properties and reduction in the yield of black pepper for each standard over years suggest a declining trend in the productivity of this system, probably induced by the ageing of the stand as well as the heavy management practice followed.